Production and operations management : - Heizer, Jay (Prentice Hall., 1993)
Designed for an introductory course in production and operations management, this text aims to be easy-to-read and is structured around the theme of strategy and tactics. It introduces, and integrates throughout, an emphasis on world classs manufacturing, competitive advantage and strategy, and domestic and international real-world applications. Features include: expanded coverage of quality assurance; discussion of both manufacturing and service operations; expanded coverage of location analysis and POM strategy and productivity; updated and expanded coverage of flexible manufacturing; just-in-time; MRP; computer-integrated manufacturing; Taguchi Methods; and expert systems. Supplements available include an instructor's manual and study guide.